2017
DOI: 10.5604/01.3001.0010.2776
|View full text |Cite
|
Sign up to set email alerts
|

Wait Time for Curative Intent Radio Frequency Ablation is Associated with Increased Mortality in Patients with Early Stage Hepatocellular Carcinoma

Abstract: Incremental 30-day wait times are associated with a 9% increased risk of residual tumor and a 23% increased risk of death. We have identified system gaps where quality improvement measures can be implemented to reduce wait times and allocate resources for future RFA treatment, which may improve both quality and efficiency of HCC care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 10 publications
0
24
1
Order By: Relevance
“…In one US study, treatment delays were associated with worse survival. 19 Smaller studies in Taiwan 29,48 and Canada 49 have also shown the adverse impact of delays in locoregional therapy on treatment response and survival. In contrast, studies have found that delays in surgical therapy have no impact 50 or are associated with improved survival compared with no delays.…”
Section: Discussionmentioning
confidence: 99%
“…In one US study, treatment delays were associated with worse survival. 19 Smaller studies in Taiwan 29,48 and Canada 49 have also shown the adverse impact of delays in locoregional therapy on treatment response and survival. In contrast, studies have found that delays in surgical therapy have no impact 50 or are associated with improved survival compared with no delays.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the fifth most frequently occurring cancer and the third leading cause of cancer-related death. 1 , 2 Most patients are found in the advanced stage, and the prognosis of HCC is extremely poor due to the frequent metastasis, relapse, and chemotherapy resistance. 3 5 Therefore, understanding the molecular mechanisms underlying the initiation and development of HCC may lead to the improvement of clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological results showed that 9.5% of the patients had cirrhosis, 27.6% had microvascular invasion, 12.1% had venous thromboembolism, and 88.4% were highly differentiated. Severe complications occurred in 2.6% of the patients, with a median hospital stay of 18 (14)(15)(16)(17)(18)(19)(20)(21)(22) days. The median OS of patients was 37 (23.4-57.6) months (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, several studies have shown that delayed treatment increases the risk of residual tumor and death, and delayed treatment of HCC is associated with shortened OS, and signi cantly delayed treatment leads to worse survival rates, especially in patients with delayed treatment of more than 3 months [3,[13][14][15][16] . This is contrary to the results obtained in this study.…”
Section: Discussionmentioning
confidence: 99%